Fabrication of chemical sensor for organochlorine pesticide detection using colloidal gold nanoparticles. (16th July 2018) - Goel, Puja; Arora, Manju
Abstract: Abstract : Gold nanoparticles (GNPs) of ~8 nm in diameter were used for the detection of organochlorine endosulfan pesticide (ESP) as colorimetric sensor and the design of GNP-based chemical sensor for its quantitative estimation has also been proposed. The original wine red color of GNPs changes into various shades of blue after the addition of different concentrations of ESP solutions. A GNP-based sensing electrode has been used for designing of ESP detection chemical sensor at ambient temperature. The response and sensitivity of ESP sensor parameters are obtained from their recovery curves of the change in resistance versus time.